Reduction in mortality from implantable cardioverter-defibrillators in non-ischaemic cardiomyopathy patients is dependent on the presence of left ventricular scar. (10th August 2018) - Gutman, Sarah J; Costello, Benedict T; Papapostolou, Stavroula; Voskoboinik, Aleksandr; Iles, Leah; Ja, Johnson; Hare, James L; Ellims, Andris; Kistler, Peter M; Marwick, Thomas H; Taylor, Andrew J
Abstract: Aims: In patients with non-ischaemic cardiomyopathy (NICM), the mortality benefit of a primary prevention implantable cardioverter-defibrillator (ICD) has been challenged. Left ventricular (LV) scar identified by cardiac magnetic resonance (CMR) imaging is associated with a high risk of malignant arrhythmia in NICM. We aimed to determine the impact of LV scar on the mortality benefit from a primary prevention ICD in NICM. Methods and results: We recruited 452 consecutive heart failure patients [New York Heart Association (NYHA) Class II/III] with NICM and LV ejection fraction ≤35% from a state-wide CMR service. All patients fulfilled European Society of Cardiology guidelines for primary prevention ICD implantation; however, the decision to implant was at the treating physician's discretion. Baseline clinical and CMR data were recorded prospectively and heart failure mortality risk (MAGGIC score) was calculated. The primary study outcome measurement was all-cause mortality based on presence or absence of ICD, stratified by LV scar. Median follow-up was 37.9 months and there was no difference in MAGGIC score between those who did and did not receive a primary prevention ICD (19.30 ± 5.46 vs. 18.90 ± 5.67, P = 0.50). In patients without LV scar, ICD implantation was not associated with improved mortality [hazard ratio (HR) = 1.22, 95% confidence interval (CI): 0.53–2.78, P = 0.64]. In patients with LV scar, ICD implantation was independently associated with reduced mortality (HR = 0.45, 95% CI: 0.26–0.77, P = 0.003). Conclusions: In patients with NICM, primary prevention ICD implantation is only associated with reduced mortality in patients with LV scar. This may enable more effective selection of NICM patients for ICD implantation compared with current guidelines.